IDENTIFIKASI DAN KLASIFIKASI BAKTERI AMILOLITIK ISOLAT TG12, TG19, DAN TG31 PENYEBAB KEMASAMAN PADA TEPUNG SAGU BASAH BERDASARKAN ANALISIS GEN 16SrDNA - Tri Gunaedi; Sebastian Margino; Langkah Sembiring; Rarastoeti Pratiwi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
16SrDNA gene were known essentialy for procaryotic life involved bacteria. The gene very concerved such as usefull for bacterial identification and classification in phylogeny tree constructed. The object of this research were identified and cllassified amylolitic bacteria TG12, TG19 and TG31 isolates, causers sourness on raw starch sago by 16SrDNA gene sequences analysis approach. The native isolates from raw starch sago under traditionality processing arround Jayapura and selected depend on activity amylolitic and organic acid productivity. Before DNA genom extraction, isolates were throught out generic assignment analysis. Futhermore DNA genom were amplified and purified by PCR with 27f and 1529r primers. The pure of DNA was sequenced by ABI PRISM 310 DNA sequencer with internal primers 27f, 357f, 790f and 1230f. The generic assignment resulted those isolates related with Bacillus. The 16S rDNA data were aligned with corresponding available Bacillus sequences retrieved from the NCBI database using the CLUSTAL X software. Phylogeny tree was constructed by PHYLIP programme and visualized by Treeview programme. Phylogenetic trees were and the extended the value of 16S rDNA sequencing in amylolitic bacteria causing sourness on raw starch sago. Completed 16S rDNA sequence data showed that two of the tested isolate TG12 formed a distinct center of diversity with Bacillus substilis DSM 10 AJ276351, isolate TG19 with Bacillus substilis strain 1778 EU982544 and TG31 similar genetic with Bacillus cereus strain WJL-063 FJ527559. Identification based on 16S rDNA gene sequences of amylolitic bacteria causing sourness on raw sago starch provided a powerful way of uncovering genetic of strain within the spesies Bacillus substilis and Bacillus cereus.